Emotional Labor and Self-Efficacy as Foundations of Work Resilience - Pradika Rakasiwy, Mochamad Randy (Faculty of Ushuluddin and Humanities, 2025)
This study investigates the influence of emotional labor and self-efficacy on work resilience among customer service employees in emotionally demanding roles. The topic was chosen due to the increasing psychological challenges faced by frontline workers, particularly in collectivist cultures like Indonesia, where emotional expression is tightly regulated. It was hypothesized that emotional labor and self-efficacy would both positively predict work resilience. A quantitative correlational design was employed, involving 92 customer service employees from retail companies. Data were collected using validated psychological scales and analyzed using Pearson correlation and multiple linear regression with bootstrapping. Results showed that both emotional labor and self-efficacy significantly predicted work resilience (R² = 0.640, p < 0.001), with self-efficacy as the dominant predictor (β = 0.217; t = 6.816) over emotional labor (β = 0.193; t = 4.238). These findings highlight the dual role of emotion regulation and personal belief systems in sustaining resilience under emotional demands. The study offers practical implications for employee development programs in service industries. Keywords: Emotional Labor, Self-Efficacy, Work Resilience, Customer Service